LEPR q223r gene polymorphism in patients having coronary heart disease with postinfarction cardiosclerosis and type 2 diabetes - Абдуллах, Аль Салім Аяд; Станіславчук, Микола Адамович; Заічко, Наталія Валентинівна (ScienceRise: Medical Science, 2017)
Aim. To determine the prevalence of mononucleotide leptin receptor gene LEPR Q223R polymorphism in patients having coronary heart disease (CHD) with postinfarction cardiosclerosis depending on type 2 diabetes comorbidity. Materials and methods. 147 patients having stable CHD with postinfarction cardiosclerosis (100% male), the average age of 52, were examined. In 64 (43.5%) patients CHD combined with type 2 diabetes. The CHD diagnosis was established by АНА/АСС (2014) and ESC (2013) recommendations. LEPR Q223R (Gln223Arg, rs1137101) gene polymorphism was determined using allele-specific polymerase chain reaction in real time. Results and discussion. In the group of patients having CHD with postinfarction cardiosclerosis (Podillya region inhabitants) the frequency of LEPR Q223R gene genotypes was as follows: QQ – 25.2 %, QR – 42.4 %, RR – 32.7 %. The frequency of R allele in patients having CHD was significantly higher than in the practically healthy group, and was 53.7 to 41.3% (χ2=4.72, р=0.03). Сomorbidity chances significantly increase in R allele carriers (OR=1.58, 95 % СІ 0.99-2.53), while Q allele carrier state have a protective value (OR=0.63, 95 % СІ 0.40-1.01). RR genotype associated with CHD earlier debut, higher frequency of Q- myocardial infarction (OR=4.3; 95 % СІ 1.51-12.5) and heart failure progression (OR=3.60; 95 % СІ 1.67-7.77). Conclusion. RR genotype LEPR Q223R gene carrier state is a potential unmodified factor that accelerates development and increases the severity of CHD, associated with type 2 diabetes, in males